Enhanced In Vitro Antiviral Activity of Hydroxychloroquine Ionic Liquids against SARS-CoV-2 - Francisco Faísca; Vanessa Correia; Željko Petrovski; Luís C. Branco; Helena Rebelo-; Miguel M. Santos (MDPI AG, 2022)
The development of effective antiviral drugs against SARS-CoV-2 is urgently needed and a global health priority. In light of the initial data regarding the repurposing of hydroxychloroquine (HCQ) to tackle this coronavirus, herein we present a quantitative synthesis and spectroscopic and thermal characterization of seven HCQ room temperature ionic liquids (HCQ-ILs) obtained by direct protonation of the base with two equivalents of organic sulfonic, sulfuric and carboxylic acids of different polarities. Two non-toxic and hydrophilic HCQ-ILs, in particular, [HCQH2][C1SO3]2 and [HCQH2][GlcCOO]2, decreased the virus-induced cytopathic effect by two-fold in comparison with the original drug, [HCQH2][SO4]. Despite there being no significant differences in viral RNA production between the three compounds, progeny virus production was significantly affected (p < 0.05) by [HCQH2][GlcCOO]2. Overall, the data suggest that the in vitro antiviral activities of the HCQ-ILs are most likely the result of specific intra- and intermolecular interactions and not so much related with their hydrophilic or lipophilic character. This work paves the way for the development of future novel ionic formulations of hydroxychloroquine with enhanced physicochemical properties.